Kritik Terhadap Mu’tazilah dalam Kitab Tarjamah Sabīl al-Abīd ‘ala Jauharah al-Tauhīd Karya Kiai Sholeh Darat - Rusdiyanto, Rusdiyanto; Hafsah, Umi (FIKRAH, 2023)
The book Tarjamah Sabīlul al-Abīd 'ala Jauharah al-Tauhīd by Kiai Sholeh Darat is one of the legacies of the Islamic theology of the Archipelago which has had a significant influence on Islamic mindsets, especially among Islamic boarding schools. One of the important and exciting discussions in the book described in this article is a critique of the Mu'tazilah teachings in matters of aqidah, using library data to obtain primary and secondary data and a philosophical hermeneutic approach that emphasizes verstehen (understanding) and interpretation elements. Two important points were found in this article: First, according to the teachings of Kiai Sholeh Darat Mu'tazilah, which states that the mind can know God is a mistake because it negates the shari'ah. Second, Kiai Sholeh Darat also criticized the Mu'tazilah teachings regarding Usul al-Khomsah as the core teachings of the Mu'tazilah. Even this criticism is quite complete because it covers core issues such as the qadim and the hadith of kalamullah, whether or not God's nature exists or not, free will, God's justice, and the position of humans who commit major sins.